Prevalence of chronic pain in the UK: a systematic review and meta-analysis of population studies. Issue 6 (20th June 2016) - Fayaz, A; Croft, P; Langford, R M; Donaldson, L J; Jones, G T
Abstract : Objectives: There is little consensus regarding the burden of pain in the UK. The purpose of this review was to synthesise existing data on the prevalence of various chronic pain phenotypes in order to produce accurate and contemporary national estimates. Design: Major electronic databases were searched for articles published after 1990, reporting population-based prevalence estimates of chronic pain (pain lasting >3 months), chronic widespread pain, fibromyalgia and chronic neuropathic pain. Pooled prevalence estimates were calculated for chronic pain and chronic widespread pain. Results: Of the 1737 articles generated through our searches, 19 studies matched our inclusion criteria, presenting data from 139 933 adult residents of the UK. The prevalence of chronic pain, derived from 7 studies, ranged from 35.0% to 51.3% (pooled estimate 43.5%, 95% CIs 38.4% to 48.6%). The prevalence of moderate-severely disabling chronic pain (Von Korff grades III/IV), based on 4 studies, ranged from 10.4% to 14.3%. 12 studies stratified chronic pain prevalence by age group, demonstrating a trend towards increasing prevalence with increasing age from 14.3% in 18–25 years old, to 62% in the over 75 age group, although the prevalence of chronic pain in young people (18–39 years old) may be as high as 30%. Reported prevalence estimates were summarised for chronic widespread pain (pooled estimate 14.2%, 95% CI 12.3% to 16.1%; 5 studies), chronic neuropathic pain (8.2% to 8.9%; 2 studies) and fibromyalgia (5.4%; 1 study). Chronic pain was more common in female than male participants, across all measured phenotypes. Conclusions: Chronic pain affects between one-third and one-half of the population of the UK, corresponding to just under 28 million adults, based on data from the best available published studies. This figure is likely to increase further in line with an ageing population.